2021
DOI: 10.7759/cureus.19298
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Single Lateral Locked Plate and Double Locked Plate Application in the Treatment of Bicondylar Tibial Plateau Fractures

Abstract: Background and objective Bicondylar tibial plateau fractures (BTPFs) have been controversial in terms of surgery planning, due to articular joint surface comminution, severe soft tissue injury, and the risk of complications. The aim of this study was to conduct a clinical, functional, and radiologic comparison of the dual locked plate (DLP) and single lateral locked plate (SLLP) techniques. Methods Retrospectively analysed were 54 patients who underwent surgical treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A study by Neogi et al in 2015 also compared the 2-year follow-up of a group of 29 patients with lateral plates and a group of 32 with dual plates, finding no significant difference in the knee scores between the two groups 11 . On the other hand, a study by Çağlar et al in 2021 showed that dual plates yielded a better range of motion values than lateral plates 12 .…”
Section: Introductionmentioning
confidence: 96%
“…A study by Neogi et al in 2015 also compared the 2-year follow-up of a group of 29 patients with lateral plates and a group of 32 with dual plates, finding no significant difference in the knee scores between the two groups 11 . On the other hand, a study by Çağlar et al in 2021 showed that dual plates yielded a better range of motion values than lateral plates 12 .…”
Section: Introductionmentioning
confidence: 96%